L1 vs L2 synchronous text-based interaction in computer-mediated L2 writing. (February 2020) - Yanguas, Inigo
Abstract: This study investigates the quality of the L2 written outcome and the interactions produced in synchronous text-based L1 and L2 collaboration. On the one hand, it explores fluency, accuracy, and complexity measures in order to compare participants' L2 performance in a task-based writing assignment using Google Docs. On the other hand, it examines the areas of negotiation in their L1 and L2 synchronous interactions in order to assess possible differences. Eighty-five intermediate students of Spanish were randomly assigned to four different dyadic writing groups: a control group, a collaborative L1 text-based chat group, a collaborative L2 text-based chat group, and a group of dyads who collaborated on Google Docs but were not permitted to chat. ANOVA analyses of the L2 writing measures under scrutiny showed that the dyads that collaborated in their L1 had a significant advantage in the accuracy measure utilized. Additionally, analyses of the interactions produced by the dyads in both chat groups showed that the L1 chat group conversed more but focused less on the L2. These results are discussed in relation to the relevant previous literature and should continue the discussion on translanguaging and how L1 can be of use in L2 writing.